Joint Growth Trajectories of Trait Emotional Intelligence Subdomains Among L2 Language Learners: Estimating a Second-Order Factor-of-Curves Model With Emotion Perception - Taherian, Tahereh; Fazilatfar, Ali Mohammad; Mazdayasna, Golnar (Frontiers in Psychology, 2021)
The present study assesses the developmental dynamics of TEI and its subdomainsduring learning English as a foreign language (EFL) in a longitudinal study. A sample of 309 EFL learners (217 females, 92 males) was used to assess the trajectories of the global factor of TEI as well as parallel development of the TEI subdomains over one year in the context of EFL classroom using parallel-process modeling (PPM) and factor of curve modeling (FCM). Additionally, we used emotion perception (EP) as a distal outcome in order to investigate how the growth parameters including intercept and slope factors in a TEI-FCM influence the distal outcome of EP. The results revealed that all growth parameters across the four primary growth curves were statistically significant. This confirmed a significant increase in these subdomains over time. Also, the primary growth factors of TEI subdomains differentially contributed to second-order growth factors. Moreover, the variance of the intercept and slope of each subdomain proved to be largely explained by the global factor of TEI. Additionally, concerning the covariances within and among the subdomains of TEI, the PPM results revealed moderate to high associations between intercept and slope growth factors within and between these subdomains. Finally, regarding the direct association of the global growth factors (intercept and slope) of TEI on EP, the results indicated that intercept and slope of global TEI were associated with EP. More specifically, the intercepts and slopes of emotionality and sociability turned out to be significantly linked to the EP. These results suggest the dynamicity of TEI during learning a foreign language, which are discussed in the light of the potential variables associated with TEI and its related literature.